Values, religion, and culture in adolescent development - Trommsdorff, Gisela; Chen, Xinyin (Cambridge : Cambridge University Press, 2012)
"Cultural values and religious beliefs play a substantial role in adolescent development. Developmental scientists have shown increasing interest in how culture and religion are involved in the processes through which adolescents adapt to environments. This volume constitutes a timely and unique addition to the literature on human development from a cultural-contextual perspective. Editors Gisela Trommsdorff and Xinyin Chen present systematic and in-depth discussions of theoretical perspectives, landmark studies and strategies for further research in the field. The eminent contributors reflect diverse cultural perspectives, transcending the Western emphasis of many previous works. This volume will be of interest to scholars and professionals interested in basic developmental processes, adolescent social psychology and the sociological and psychological dimensions of religion"--
Machine generated contents note: Preface Gisela Trommsdorff and Xinyin Chen; Part I. Theoretical Perspectives on Values, Religion, and Adolescent Development in Cultural Context: 1. Cultural perspectives on values and religion in adolescent development: a conceptual overview and synthesis Gisela Trommsdorf; 2. Psychological functions of religion in youths - a historical and cultural perspective Hans-Joachim Kornadt; 3. Cultural differences in self-awareness in adolescence: pathways to spiritual awareness Fred Rothbaum, Yan Wang and Dov Cohen; Part II. Universal and Culture-Specific Functions of Adolescent Values and Religion: 4. Values and religion in adolescent development: cross-national and comparative evidence Shalom Schwartz; 5. Religion and life satisfaction of young persons around the world: personal values and societal context Michael Harris Bond, Vivian Mui-Chi Lun and Liman Man Wai Li; 6. Indonesian Muslim adolescents and the ecology of religion Doran C. French, Nancy Eisenberg, Julie Sallquist and Urip Purwano; 7. Peer groups as a crucible of positive value development in a global world Reed W. Larson, Lene A. Jensen, Hyeyoung Kang, Aisha Griffith and Vikki Rompala; 8. Civic development in relational perspective Kenneth H. Rubin, Tina Malti and Kristina McDonald; Part III. Impact of Values and Religion on Adolescent Adjustment in Times of Social Change: 9. Marginalized Japanese youth in post-industrial Japan: motivational patterns, self-perceptions, and the structural foundations of shifting values Vinai Norasakkunkit and Yukiko Uchida; 10. Adolescent cultural values and adjustment in the changing Chinese society Xinyin Chen, Li Wang and Junsheng Liu; 11. With God's help: the future orientation of Palestinian girls in Israel growing up Muslim Rachel Seginer and Sami Mahajna; 12. Religion's role in the development of girls' occupational aspirations Lisa D. Pearce and Jessica Halliday Hardie; 13. First romantic relationships of adolescents from different religious groups in Israel and Germany Bernhard Nauck and Anja Steinbach; Part IV. Socialization Processes of Values and Religion in Adolescent Behavior: 14. Attachment and religious development in adolescence: the implications of culture Pehr Granqvist; 15. Cross-cultural perspectives on adolescents' religiosity and family orientation Boris Mayer and Gisela Trommsdorff; 16. Religion and the intergenerational continuity of values Ariel Knafo, Ella Daniel, Sigal Gabay, Ran Zilber and Rivka Shir; 17. Adolescents' social development and the role of religion: coherence at the detriment of openness Vassilis Saroglou; 18. Hindu religious values and their influence on youths in India Ramesh C. Mishra.
Includes bibliographical references and index.
Keywords: Adolescent psychology; Values; Religion and culture; PSYCHOLOGY / Developmental / General